Surface-Modification of Carbonate Apatite Nanoparticles Enhances Delivery and Cytotoxicity of Gemcitabine and Anastrozole in Breast Cancer Cells - Mozar, Fitya Syarifa (Pharmaceutics, 2017)
pH sensitive nanoparticles of carbonate apatite (CA) have been proven to be effective delivery vehicles for DNA, siRNAs and proteins. More recently, conventional anti-cancer drugs, such as doxorubicin, methotrexate and cyclophosphamide have been successfully incorporated into CA for intracellular delivery to breast cancer cells. However, physical and chemical properties of drug molecules appeared to affect their interactions with CA, with hydrophillic drug so far exhibiting better binding affinity and cellular uptakes compared to hydrophobic drugs. In this study, anastrozole, a non-steroidal aromatase inhibitor which is largely hydrophobic, and gemcitabine, a hydrophilic nucleoside inhibitor were used as solubility models of chemotherapy drug. Aggregation tendency of poorly soluble drugs resulting in larger particle-drug complex size might be the main factor hindering their delivery effectiveness. For the first time, surface modification of CA with poly(ethylene glycol) (PEG) has shown promising result to drastically reduce anastrozole- loaded CA particle size, from approximately 1000 to 500 nm based on zeta sizer analysis. Besides PEG, a cell specific ligand, in this case fibronectin, was attached to the particles in order to facilitate receptor mediated endocytosis based on fibronectin–integrin interaction. High-performance liquid chromatography (HPLC) was performed to measure uptake of the drugs by breast cancer cells, revealing that surface modification increased the drug uptake, especially for the hydrophobic drug, compared to the uncoated particles and the free drug. In vitro chemosensitivity assay and in vivo tumor regression study also showed that coated apatite/drug nanoparticle complexes presented higher cytotoxicity and tumor regression effects than uncoated apatite/drug nanoparticles and free drugs, indicating that surface modification successfully created optimum particles size with the consequence of more effective uptake along with favorable pharmacokinetics of the particles.